Physicochemical characterization of drug nanocarriers - Manaia EB (Dove Medical Press, 2017)
Eloísa Berbel Manaia,1 Marina Paiva Abuçafy,1 Bruna Galdorfini Chiari-Andréo,1,2 Bruna Lallo Silva,1 João Augusto Oshiro Junior,1 Leila Aparecida Chiavacci1 1Department of Drugs and Medicines, School of Pharmaceutical Sciences, São Paulo State University (UNESP), Araraquara, SP, Brazil, 2Department of Biological and Health Sciences, Centro Universitário de Araraquara, UNIARA, Araraquara, SP, Brazil Abstract: Pharmaceutical design has enabled important advances in the prevention, treatment, and diagnosis of diseases. The use of nanotechnology to optimize the delivery of drugs and diagnostic molecules is increasingly receiving attention due to the enhanced efficiency provided by these systems. Understanding the structures of nanocarriers is crucial in elucidating their physical and chemical properties, which greatly influence their behavior in the body at both the molecular and systemic levels. This review was conducted to describe the principles and characteristics of techniques commonly used to elucidate the structures of nanocarriers, with consideration of their size, morphology, surface charge, porosity, crystalline arrangement, and phase. These techniques include X-ray diffraction, small-angle X-ray scattering, dynamic light scattering, zeta potential, polarized light microscopy, transmission electron microscopy, scanning electron microcopy, and porosimetry. Moreover, we describe some of the commonly used nanocarriers (liquid crystals, metal–organic frameworks, silica nanospheres, liposomes, solid lipid nanoparticles, and micelles) and the main aspects of their structures. Keywords: nanoparticles, drug delivery, physicochemical properties, controlled drug release